The Complete Chi's Sweet Home - Part 3 - Kanata, Konami 1958-.; Chavez, Ed (New York, NY : Vertical, Inc., 2015)
"Chi is a mischievous newborn kitten who, while on a leisurely stroll with her family, finds herself lost. Separated from the warmth and protection of her mother, feels distraught. Overcome with loneliness she breaks into tears in a large urban park meadow, when she is suddenly rescued by a young boy named Yohei and his mother. The kitty is then quickly and quietly whisked away into the warm and inviting Yamada family apartment where pets are strictly not permitted. The Complete Chis Sweet Home collects Chis Sweet Home vol 1, Chis Sweet Home vol 2 and Chis Sweet Home vol 3 and includes never before translated comics from Konami Kanata in a new larger trim size!"--provided from Amazon.com.
"First published in Japan in 2004, 2005, 2006 by Kodansha Ltd. Tokyo"--Colophon.
Keywords: Kittens -- Comic books, strips, etc; Juvenile fiction; Cat owners -- Comic books, strips, etc; Juvenile fiction; Human-animal relationships -- Comic books, strips, etc; Juvenile fiction; Graphic novels